PRIMARY PRODUCTIVITY OF THI NAI LAGOON, BINH DINH PROVINCE - Trang, Cao Thi Thu; Dieu, Luu Van; Sinh, Le Xuan; Thanh, Tran Duc (Vietnam Journal of Marine Science and Technology, 2015)
Experiments of photosynthesis assessment of phytoplankton and seaweed had been carried out in Thi Nai lagoon in rainy season (October, 2013) and dry season (May, 2014). The results showed that primary productivity of phytoplankton was 8 - 149 mgC/m3/day, and that productivity of seaweed Gracilaria verrucosa was 0.139 - 0.197 mg C/g seaweed/day. During photosynthesis process of phytoplankton, an amount of 1.42 - 1.6 tons mineral nitrogen/day and 0.14 - 0.17 tons phosphate/day was consumed in the whole lagoon. The photosynthesis process of seaweed also consumed an amount of 0.74 - 0.83 tons/day of inorganic nitrogen (including nitrate, nitrite, and ammonium), and 0.041 - 0.045 tons/day of phosphate in the whole lagoon.